Proceso de atención de enfermería en paciente diabético con gangrena de fournier - Espinoza Delgado, Nuvia Fernanda (2024)
Fournier's gangrene is a rare but serious infectious disease of necrotizing fasciitis that primarily affects the genital and perineal areas, representing a significant challenge in clinical practice. The case study focused on implementing the nursing care process in the diabetic patient with Fournier's gangrene, through the nursing care plan to optimize health outcomes and quality of life. Data collection was carried out through clinical history, medical evaluation and laboratory tests, interventions were implemented based on the total assessment of Marjory Gordon's functional patterns and the NANDA, NOC and NIC taxonomies, which allowed detailed information to be collected. about the patient's condition. Interventions included wound care, infection control, protection against infection, administration of antibiotics, exercise therapy, position change, nutrition management, teaching: disease process and reduction of transfer stress, which were essential in recovery of the patient. Through the teaching provided by nursing, the patient expanded her knowledge about her illness, which led to better self-care management and requested her discharge by her own decision. A key intervention was education on hygiene and the use of antimicrobials, reducing nosocomial infections significantly. Despite the positive results, the study faced the limitation of a shortened duration of the care plan, since discharge was requested by the patient. However, it served as a valuable guide, emphasizing the importance of continuing education and an evidence-based approach in nursing practice.